Analytical Method Development And Validation For The Estimation Of Serratiopeptidase Using Spectrophotometry - Chauhan, Mamta; Saini, Rita; Patil, Shivanand (Journal of Neonatal Surgery, 2025)
This study focuses on develop a simple, reliable, and cost effective analytical method for accurately measuring serratiopeptidase, a clinically significant anti-inflammatory and proteolytic enzyme, using UV-Visible spectrophotometry. Serratiopeptidase is a proteolytic enzyme.and has various therapeutic treatment mostly used as an anti-inflammatory and analgesic agent. And it makes accurate quantification in pharmaceutical formulation crucial for quality control and regulatory compliance. UV spectrophotometry is a affordable , simple, and mostly used for this purpose. Currently, analytical methods such as HPLC and ELISA are commonly employed for the estimation of serratiopeptidase, but these techniques are often costly, require advanced instrumentation, and involve complex sample preparation, which may not be feasible for routine quality control, particularly in small-scale pharmaceutical industries or academic research laboratories.This review summarizes the current strategies for the method development of serratiopeptidase estimation using UV spectrophotometry. Key parameters such as wavelength selection, solvent choice, sample preparation, method validation, and potential interferences are discussed to highlight the advantages and limitations of UV-based methods.